Enhancement in Graphitization of Ordered Mesoporous Carbon by Assistance of Soybean Oil Surfactant - Thu Hang, Le Thi; Bich Thuy, Hoang Thi (VNU Journal of Science: Natural Sciences and Technology; Vol 36 No 3, 2020)
In this work, highly ordered mesoporous graphitic carbon (G-CMK3) has been prepared successfully by a nano-casting method using sucrose as carbon source, mesoporous silica as hard template, and soybean oil as surfactant. In the absence of soybean oil surfactant, the synthesized ordered mesoporous carbon material, CMK-3, revealed a low graphitization degree with a specific surface area of 1049.1 m 2 /g and a high pore volume of 1.172 cm 3 /g.  However, with the assistance of soybean oil surfactant, the graphitization degree was improved significantly, which was confirmed by the decrease in the I D /I G intensity ratio of the D (disordered or amorphous structure) and G (graphitic structure) peaks from 0.98 to 0.83. After the synthesis in the presence of soybean oil, G-CMK3 carbon maintained the integrity of the mesoporous structure albeit with a slight decrease in its specific surface area (845.2 m 2 /g) as well as pore volume (0.858 cm 3 /g).